(untitled) (Comprehensive Journal of Science, 2025)
The study addressed the impact of organization behavior management on the a quantity of education service provided. Applet to Al-furat private university. The study problem ubs represented in a main question. What are the impacts of organizational behavior management on the quality of educational services provided to Al-Furat private university? The study aimed to determine. The eytont of the impact of organizational behavior. On the quantity of educational service’s provided to all – Furat private university . then apply the disruptive and analytical approach and the questionnaire. The study concluded with a number of results, the most imp Orland of which are: the demographic data chow a the largest age group is the group ranging from 30 to40 years and that the most comman academic degree